Implementasi Profil Pelajar Pancasila dan Implikasinya terhadap Karakter Siswa di SDIT Insan Qurani Sumbawa - Ida Aulia Mawaddah; Abdul Haris (Al-Munawwarah : Jurnal Pendidikan Islam, 2022)
This study aims to see how the implementation of the Pancasila Student Profile program in the Independent Curriculum is implemented at SDIT Insan Qurani Samawa Sumbawa Besar, as well as to see whether this Pancasila Student Profile has a good impact on the character of students. In this study it was found that the implementation of the Pancasila Student Profile was considered optimal at SDIT Insan Qurani Samawa Sumbawa Besar because from the start the school had built a vision and mission that was in line with the six characteristics of the Pancasila Student Profile. Student participation in the implementation of the Pancasila Student Profile is very good as can be seen from the active role of students and teachers in learning both inside and outside the classroom because in our souls and attitudes every day in the community or profession, we are obliged to instill the Pancasila Student Profile in ourselves